Incidence, risk factors, and prognosis of patients with hepatocellular carcinoma and brain metastases - Feng, Jincheng; He, Ying; Polychronidis, Georgios; Xin, Jian; You, Shen; Xiong, Jun (Current medical science, 2024)
OBJECTIVE: Brain metastases significantly impact the clinical course of patients with hepatocellular carcinoma (HCC). This study aimed to examine the age-related incidence, demographics, and survival of patients with HCC and brain metastases. - METHODS: Data of HCC patients from 2010 to 2015 in the Surveillance, Epidemiology, and End Results (SEER) Registry were screened for the presence of brain metastases. They were stratified by age and ethnicity. Multivariable logistic and Cox regression analyses were used to identify factors associated with brain metastases and those with overall survival (OS) and liver cancer-specific survival (CSS), respectively. - RESULTS: A total of 141 HCC patients presenting with brain metastases were identified, accounting for 0.35% of all HCC patients and 2.37% of patients with metastatic disease. Among all HCC patients, the incidence rate was the highest among patients aged 30-49 years old (0.47%). Ethnicity was not associated with the presence of brain metastases at the time of HCC diagnosis. However, African-American patients presented with a significantly lower disease-specific survival [median time: 1 month; interquartile range (IQR): 0-3.0 months)]. Initial lung or bone metastasis was independently associated with an increased risk of the presence of brain metastases [odds ratio (OR): 12.62, 95% confidence interval (CI): 8.40-18.97] but was not associated with a worse OS or CSS among those with brain metastases. - CONCLUSION: This study identified the age-related incidence and risk factors of brain metastases in HCC patients. These results may contribute to the consideration of brain screening among patients with initial metastatic HCC with lung or bone metastases, and influence the counseling of this patient population regarding their prognosis.
Online veröffentlicht: 23 February 2024
Gesehen am 06.06.2025